Novel bird’s-foot trefoil RNA viruses provide insights into a clade of legume-associated enamoviruses and rhabdoviruses - Debat, Humberto Julio (2019)
Here, we report the identification and characterization of two novel viruses associated with bird’s-foot trefoil. Virus sequences related to those of enamoviruses (ssRNA (+); Luteoviridae; Enamovirus) and nucleorhabdoviruses (ssRNA (-); Rhabdoviridae; Nucleorhabdovirus) were detected in Lotus corniculatus transcriptome data. The genome of the tentatively named “bird’s-foot trefoil-associated virus 1” (BFTV-1) is a 13,626-nt-long negative-sense ssRNA. BFTV-1 encodes six predicted gene products in the antigenome orientation in the canonical order 3′-N-P-P3-M-G-L-5′. The genome of the proposed “bird’s-foot trefoil-associated virus 2” (BFTV-2) is 5,736 nt long with a typical 5΄-PO-P1-2-IGS-P3-P5-3′ enamovirus genome structure. Phylogenetic analysis indicated that BFTV-1 is closely related to datura yellow vein nucleorhabdovirus and that BFTV-2 clusters into a monophyletic lineage of legume-associated enamoviruses. This subclade of highly related and co-divergent legume-associated viruses provides insights into the evolutionary history of the enamoviruses.